PR3ANCA Related Cerebral Vasculitis in Ulcerative Colitis Presenting with Orbital Involvement: A Case Report with Review of Literature - Athira Unnikrishnan; Shila Azodi; Nadeem Ansari; Megan Brown; Joshua Kamnetz; Robert C. Uchiyama (Case Reports in Rheumatology)
PR3 ANCA is a classic marker of granulomatosis with polyangiitis (GPA). There have been several recent reports of increased prevalence of PR3ANCA in ulcerative colitis (UC) patients, the clinical implication of which is not well defined. We are reporting a case of 27-year-old Caucasian male with 14-year history of UC presenting with unilateral proptosis, conjunctival congestion, and chemosis who developed acute hemiparesis within three days of hospital admission, followed by rapid neurological deterioration correlating with brain imaging findings. Serologically he had atypical PANCA with high PR3 antibody titer with a negative infectious workup. His cerebral angiogram was normal but the brain biopsy showed necrotizing vasculitis. He was diagnosed with PR3 ANCA mediated cerebral and orbital vasculitis associated with UC. Treatment was initiated with high dose steroids, plasmapheresis, and cyclophosphamide. He improved significantly with residual left hemiparesis.